Surveillance of Helicobacter pylori Antibiotic Susceptibility in Indonesia: Different Resistance Types among Regions and with Novel Genetic Mutations. - Muhammad Miftahussurur; Ari Fahrial Syam; Iswan Abbas Nusi; Dadang Makmun; Langgeng Agung Waskito; Lukman Hakim Zein; Fardah Akil; Willy Brodus Uwan; David Simanjuntak; I Dewa Nyoman Wibawa; Jimmy Bradley Waleleng; Alexander Michael Joseph Saudale; et al. (PLoS ONE, 2016)
Information regarding Helicobacter pylori antibiotic resistance in Indonesia was previously inadequate. We assessed antibiotic susceptibility for H. pylori in Indonesia, and determined the association between virulence genes or genetic mutations and antibiotic resistance. We recruited 849 dyspeptic patients who underwent endoscopy in 11 cities in Indonesia. E-test was used to determine the minimum inhibitory concentration of five antibiotics. PCR-based sequencing assessed mutations in 23S rRNA, rdxA, gyrA, gyrB, and virulence genes. Next generation sequencing was used to obtain full-length sequences of 23S rRNA, infB, and rpl22. We cultured 77 strains and identified 9.1% with clarithromycin resistance. Low prevalence was also found for amoxicillin and tetracycline resistance (5.2% and 2.6%, respectively). In contrast, high resistance rates to metronidazole (46.7%) and levofloxacin (31.2%) were demonstrated. Strains isolated from Sumatera Island had significantly higher metronidazole resistance than those from other locations. Metronidazole resistant strains had highly distributed rdxA amino acid substitutions and the 23S rRNA A2143G mutation was associated with clarithromycin resistance (42.9%). However, one strain with the highest MIC value had a novel mutation in rpl22 without an A2143G mutation. Mutation at Asn-87 and/or Asp-91 of gyrA was associated with levofloxacin-resistance and was related to gyrB mutations. In conclusions, although this is a pilot study for a larger survey, our current data show that Indonesian strains had the high prevalence of metronidazole and levofloxacin resistance with low prevalence of clarithromycin, amoxicillin, and tetracycline resistance. Nevertheless, clarithromycin- or metronidazole-based triple therapy should be administered with caution in some regions of Indonesia.